Research on the Measurement of Logistics Capability of Core Cities along “the Belt and Road” in China - Zhichao Sun; Tao Wang; Xinuo Xiao; Qing Zhang; Huiwen Guo (Advances in Mathematical Physics)
The B&R strategy came into being to promote the free and orderly flow of economic factors, the efficient allocation of resources, and the depth of market integration. Logistics is the artery of element circulation and the basis of the B&R. The logistics capacity of core cities along the R&B will be an essential factor affecting the strategy. In this context, it is of practical significance to measure the logistics capacity of the core cities along the B&R. Since combing domestic and overseas research, this paper first uses clustering analysis to screen out nine core cities along the B&R and then uses fuzzy matter-element analysis to measure their urban logistics capacity and sort them. The results show that the urban logistics capacity in the eastern coastal areas of China is higher than that in northwest and southwest China. The logistics capacity of cities along “The 21st Century Sea Silk Road” is more robust than that of others and through the urban agglomeration could further achieve economies of scale. The logistics capacity of cities along the “Silk Road Economic Zone” should improve the construction of logistics infrastructure and enhance logistics information in the future.